The implications of orbital invasion in sinonasal tract malignancies. (2nd September 2016) - Muscatello, Luca; Fortunato, Susanna; Seccia, Veronica; Marchetti, Manuela; Lenzi, Riccardo
ABSTRACT: In recent decades, the management of sinonasal tumors abutting the orbit has been widely discussed. A real guideline has yet to be proposed, as prospective randomized studies on this topic are very difficult to organize, given the relative rarity of this pathology, the wide spectrum of histologic patterns, and the different clinical behavior of tumors. Nevertheless, in recent years, a better assessment of tumor extension has been obtained thanks to the refinement of preoperative imaging tools and, therefore, more conservative approaches could be adopted, with no worsening of the oncological outcomes and, at the same time, with more attention given to the post-surgical quality of life. Currently, tumors that extend to the bony orbital walls with or without focal infiltration of the periorbit are amenable to orbital preservation. On the other hand, infiltration of extraocular muscles and neurovascular structures are an indication to orbital exenteration. The ideal surgical treatment in cases of limited involvement of orbital fat still remains a matter of debate. We report and discuss the recent English literature on this interesting topic.